ROTASI KAP DAN FEE AUDIT SERTA PENGARUHNYA TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Andi Nur Azisah; Zikra Supri; Riyanti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
This study aims to examine the effect of Public Accounting Firm Rotation (KAP) and Audit Fees on audit quality in manufacturing companies listed on the Indonesia Stock Exchange. This study used a quantitative method using 43 samples from manufacturing companies and processed using the Statistical Program for Social Science (SPSS). The results of this study show that audit rotation does not significantly affect audit quality and audit fees affect audit quality